-18-49-(-84)-27=

Simple and best practice solution for -18-49-(-84)-27= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18-49-(-84)-27= equation:


Simplifying
-18 + -49 + -1(-84) + -27 = 0

Multiply -1 * -84
-18 + -49 + 84 + -27 = 0

Combine like terms: -18 + -49 = -67
-67 + 84 + -27 = 0

Combine like terms: -67 + 84 = 17
17 + -27 = 0

Combine like terms: 17 + -27 = -10
-10 = 0

Solving
-10 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 10x=1390-15y | | 16x-(7x-8)=71 | | 3(3z+2)-7=71 | | 5y=-x-1 | | z-74= | | 102/200 | | f-19= | | 5r+6-2r=7r-19 | | -10=y+14 | | 4y(5x-y)= | | X/8=x-63 | | 24+c= | | 10x+15y=1390 | | 9(x+6)-3=51 | | (4x^2y^8)(-3x^3y)= | | 33+x=49 | | -30-(-65)-29-4= | | X^2-64=9 | | 3x^7+5x^3=1000000000000000 | | 4b*7=x | | 9=-3(21-y)+2(y-4) | | -32t=0 | | 9(x+3)+4=11x-2(x-5) | | 16t^2=0 | | 7+h=-12 | | -6p+8+7p=17 | | 9x+16=6x+4+4x-2 | | 17.9-x=12.8 | | 413=7(-7x-18) | | 4u-13=51 | | 8x/9-6=58 | | a+(-6)= |

Equations solver categories